The Chara Genome: Secondary Complexity and Implications for Plant Terrestrialization - Nishiyama, Tomoaki; Sakayama, Hidetoshi; de Vries, Jan; Buschmann, Henrik; Saint-Marcoux, Denis; Ullrich, Kristian K; Haas, Fabian B; Vanderstraeten, Lisa; Becker, Dirk; Lang, Daniel; Vosolsobě, Stanislav; Rombauts, Stephane; et al. (Cell, 2018)
Land plants evolved from charophytic algae, among which Charophyceae possess the most complex body plans. We present the genome of Chara braunii; comparison of the genome to those of land plants identified evolutionary novelties for plant terrestrialization and land plant heritage genes. C. braunii employs unique xylan synthases for cell wall biosynthesis, a phragmoplast (cell separation) mechanism similar to that of land plants, and many phytohormones. C. braunii plastids are controlled via land-plant-like retrograde signaling, and transcriptional regulation is more elaborate than in other algae. The morphological complexity of this organism may result from expanded gene families, with three cases of particular note: genes effecting tolerance to reactive oxygen species (ROS), LysM receptor-like kinases, and transcription factors (TFs). Transcriptomic analysis of sexual reproductive structures reveals intricate control by TFs, activity of the ROS gene network, and the ancestral use of plant-like storage and stress protection proteins in the zygote.
Keywords: genom rostlinný; biologická evoluce; Pentosyltransferases; transkripční faktory; Genome, Plant; genové regulační sítě; reactive oxygen species; Plant Proteins; plant evolution; Reactive Oxygen Species; Transcription Factors; Protein Serine-Threonine Kinases; Gene Regulatory Networks; rostlinné proteiny; vyšší rostliny; Phragmoplastophyta; phytohormones; buněčná stěna; pentosyltransferasy; reaktivní formy kyslíku; Chara; phragmoplast; transkriptom; charophyte; regulátory růstu rostlin; transcriptional regulation; Biological Evolution; Transcriptome; Embryophyta; protein-serin-threoninkinasy; Cell Wall; Plant Growth Regulators; streptophyte